2017
DOI: 10.1007/s00774-017-0865-0
|View full text |Cite
|
Sign up to set email alerts
|

Teriparatide rapidly improves pain-like behavior in ovariectomized mice in association with the downregulation of inflammatory cytokine expression

Abstract: Recent studies have indicated that teriparatide, an anti-osteoporosis agent, significantly improves back pain regardless of the presence of vertebral fracture in osteoporosis patients. The aims of this study were to examine whether teriparatide improves pain-like behavior in an ovariectomized (OVX) mouse model, and to evaluate changes in osteoclast marker levels and inflammatory cytokine expression levels induced by teriparatide treatment in bone tissue in association with improvements in pain-like behavior. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Whilst the main source of pain in osteoporotic patients is typically considered to be complex or micro fractures due to the lower bone mineral density [13,14], a subset of these patients have pain without showing signs of fracture suggesting that osteoporotic bone loss itself can be painful [38,39]. This is supported by numerous reports of mice developing mechanical and thermal hypersensitivity following OVX surgery [40,41]. Here, we show a similar pain-like phenotype, with OVX mice developing mechanical and thermal hypersensitivity 1 week postsurgery whilst naturalistic behaviour remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the main source of pain in osteoporotic patients is typically considered to be complex or micro fractures due to the lower bone mineral density [13,14], a subset of these patients have pain without showing signs of fracture suggesting that osteoporotic bone loss itself can be painful [38,39]. This is supported by numerous reports of mice developing mechanical and thermal hypersensitivity following OVX surgery [40,41]. Here, we show a similar pain-like phenotype, with OVX mice developing mechanical and thermal hypersensitivity 1 week postsurgery whilst naturalistic behaviour remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the analgesic effect of teriparatide, it has been reported that the VAS of low back pain in patients with fresh osteoporotic vertebral fractures was significantly lower in daily and once-weekly teriparatide administration compared with risedronate [11]. Improvement in pain by teriparatide has furthermore been reported, for example, in a meta-analysis [12] and in osteoporosis animal models [13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the improvement effect on pain-like behavior in OVX mice was associated with the downregulation of inflammatory cytokine expression, including interleukin (IL)-1b, IL-6, and tumor necrosis factor-a. 31 In a recent study, although anti-IL-6 R antibody treatment had no effect on ovariectomy-induced bone loss, the treatment prevented ovariectomy-induced mechanical hyperalgesia in the hind limbs and suppressed CGRP expression in DRG neurons. 13 TPTD may inhibit bone nociceptors sensitized by lowering pH and by inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 96%